Design and implementation of BRAC University online advising application - Sharif, Hasan Ferdouse; Hussain, Nadeem; Chowdhury, Saniun Saber (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.